Prinsip Mattulu Tellue Pada Masyarakat Bone Dalam Perspektif Al-Qur’an - Mahadir . (STIU Al-Mujtama Pamekasan, 2020)
Viewing Bone People’s Principle of Mattulu Tellue from the Perspectives of Al-Quran; This study aims to describe andto know as well as to understand and to analyze Mattulu tellue principle in Bugis Bone people.In this case, it is expected to understand Matullu tellue principle in terms of its content, origins, contextualization, relationships as well as the response of the Qur’an into it.This research is a field study research using qualitative-descriptive design. In terms of its approaches, the historical, sociological, and cultural anthropological approaches were empoyed by the researcher, while the method of interpretation used was mauḍūīinterpretation method. Data were manually processed and collected through documentation, observation, and interviews. Data gained through those three data sets were then analysed using stages of data reduction, data presentation, and data conclusion drawing. The validity of the data was then tested using persistent observation and triangulation techniques. The findings of this study indicate that mattulu tellue, namely mali siparappe (washed to wash up each other), rebba sipatokkong (collapsed to uphold each other), malilu sipakainge(sinned to remind each other) is one of the Bugis Bone cultures legitimized in the daily life of Bone people. This principle leads to the concept of helping and mutual collaboration among people which hasbecome moral values inherited from the ancestor not only as a norm but also as a motto and a philosophy of life of Bugis Bone people in the hope of creating the unity. Mattulu tellue is not only a living principle by harmonizing the concepts and values of its teachings into the cultural mind, but it is also in line with the Qur'anic intellectual tradition which has become an integral part of Islamic law because it comes with Islamic values as contained in several verses of the Qur’an. KeyWords: Cultural Principle, Mattulu Tellue, Siparappe, Sipatokkong, Sipakainge, Bugis Bone,Mutual Collaboration, Unity, Helping, al-Qur’an